Efficacy of Vitamin C in Ameliorating Ochratoxicosis in Broiler Chicken - Singh, Ram; Mandal, Asit Baran (Indian Journal of Animal Nutrition, 2018)
The present study was undertaken to evaluate the efficacy of vitamin C in ameliorating ochratoxicosis in broiler chickens. Day-old broiler chicks (n=240) were divided into 6 treatment groups (T1- control (Basal diet); T2- T1 + 150 ppb OTA; T3-T1 + 100 mg vitamin C-VC; T4- T1 +200 mg VC; T5- T2 + 100 mg VC; T6- T2 + 200 mg VC per kg diet). Each diet was fed to 5 replicated groups of 8 birds each from 0 to 42 days of age. During overall growth period (0-6 weeks), the BWG of control group (T1) was higher (P